A Value - Based Segmentation Approach for Domestic Women Business Travelers - Narula, Gagandeep; Kaushik, Tanuja; Hussain, Sarah (Prabandhan: Indian Journal of Management, 2022)
The study’s objective was to explore how domestic women business travelers (DWBT) could be segmented using Kahle’s list of values (LOV). It also sought to examine whether DWBTs residing in the 5-star hotels of Delhi and Gurugram (cities in the National Capital Region of India) differed in their profiles based on demographic and tripographic variables. Questionnaires were used for gathering data from 101 DWBT. Cluster analysis was performed for developing a typology of DWBTs by using a K-means non-hierarchical partitioning procedure. The results of the study showed that a value-based segmentation of DWBTs can be created based on the LOV methodology. The findings revealed the value of security as the strongest predictor for the DWBTs falling in the value intense cluster followed by the values of self-respect and warm relationship with others, and the value of a sense of belonging holds equivalent importance to both the clusters of women belonging to value intense and value moderate clusters. Both clusters did not differ significantly in terms of any of the demographic or tripographic variables. Implementing LOV in the hotel industry would help provide an accurate framework to the hotel managers for offering products and services customized according to the values and beliefs of DWBT.